2D Log gabor and SVD based parallel texture feature extraction usingNVIDIA GPU - Raja, Sharif Ahmmad; Ratul, Aminur Rab; Niloy, Sakib Anjum (BRAC University, 2016)
Cataloged from PDF version of thesis report.